Influence of Work Engagement and Job Satisfaction on Employee Work Commitment at PT ARINDO JAYA MANDIRI - Sania Norma Amalia; Hadiahti Utami; Mellasanti Ayuwardani (Politeknik Negeri Semarang, 2025)
This study examines the influence of work engagement and job satisfaction on employee commitment at PT Arindo Jaya Mandiri, a freight forwarding and EMKL company focusing on export-import services. The research sample included all employees (n=35) using a total sampling method. Data were collected through questionnaires and literature review, and analyzed using SPSS version 25 with validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, as well as F and t tests. The results indicate that both work engagement and job satisfaction significantly influence employee commitment. The obtained multiple linear regression equation is Y = -5.786 + 0.474X1 + 0.696X2, with the two variables contributing 71.3% to employee commitment, while the remaining 28.7% is influenced by factors beyond the scope of this study.